1990
DOI: 10.3109/10408449009089875
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicological Effects and the Mode of Action of Pyrethroid Insecticides

Abstract: Neuroexcitatory symptoms of acute poisoning of vertebrates by pyrethroids are related to the ability of these insecticides to modify electrical activity in various parts of the nervous system.Repetitive nerve activity, particularly in the sensory nervous system, membrane depolarization, and enhanced neurotransmitter release, eventually followed by block of excitation, result from a prolongation of the sodium current during membrane excitation. This effect is caused by a stereoselective and structure-related in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
137
1
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(144 citation statements)
references
References 134 publications
(18 reference statements)
2
137
1
4
Order By: Relevance
“…In addition to being an acetylcholinesterase inhibitor, propoxur has recently been shown to be a tumor promoter (39). The pyrethroids are transient neurotoxins and skin and respiratory irritants (40,41). The organochlorines DDT and chlordane are neurotoxins and have been shown to be carcinogens and endrocrine disruptors in experimental bioassays (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being an acetylcholinesterase inhibitor, propoxur has recently been shown to be a tumor promoter (39). The pyrethroids are transient neurotoxins and skin and respiratory irritants (40,41). The organochlorines DDT and chlordane are neurotoxins and have been shown to be carcinogens and endrocrine disruptors in experimental bioassays (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Pyrethroids do not accumulate in the body and their excretion is rather rapid, even after repeated administrations: typically, 90% of the administered dose is excreted in urine and faeces within a week after treatment (IPCS, 1999;Aldridge, 1990;Vijverberg & van den Bercken., 1990). Studies carried out on human volunteers have shown that, after oral administration of cypermethrin doses of 0.25, 0.5, 1 and 1.5 mg/subject, about 75% of the dose is excreted in 24 hours; the rate of excretion is similar for all dosages.…”
Section: Toxicokineticsmentioning
confidence: 99%
“…Por otro lado, el estrés oxidativo a nivel del sistema nervioso, producido por cipermetrina, altera el funcionamiento normal de los receptores ionotrópicos en las membranas neuronales (Eells & Dubocovich, 1988), inhibe la actividad de la acetilcolinesterasa (Rao & Rao, 1995), retarda el cierre de los canales de sodio voltaje-dependiente (Aldridge, 1990;Vijverberg & van den Bercken, 1990) aumenta la liberación de acetilcolina de las terminaciones sinápticas, prolongando la depolarización por liberación de neurotransmisores que excitarían a neuronas vecinas (Eells et al, 1992). Estos acontecimientos producen un aumento aberrante en las concentraciones intracelulares de calcio, como un mecanismo citotóxico que puede causar su muerte mediada por la vía de la apoptosis (Jordán, 2003); y con la consecuente alteración de su citoarquitectura con una interrupción y reducción significativa de la proteína MAP2 (Abdel-Rahman et al, 2001), mostrando una alteración morfológica y, por ende, neurodegeneración (eosinofilia en soma y dendritas).…”
Section: Discussionunclassified